PERBANDINGAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS ANTARA SISWA YANG MENDAPATKAN MODEL MIND MAPPING BERBASIS PENGOPTIMALAN FUNGSI OTAK KANAN DAN MODEL PROBLEM BASED LEARNING - nurul hamidah; Sumarni Sumarni; Nuranita Adiastuty (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2019)
The purpose of study is to compare the increase in mathematical creative thinking ability between students who learn to get a mind mapping model based on optimizing right brain function and Problem Based Learning models. The research method used was a quasi experiment in the form of the pretest post-test two treatment design. The study population was seventh grade students of SMP Negeri 3 Kuningan with sampling using purposive sampling technique.The research instrument used in the form of the test instrument and non-test.The results showed that: (1) there are differences in mathematical creative thinking ability among students who get mind mapping model based on optimization of right brain function and model of Problem Based Learning; (2) there is a difference of improvement of mathematical creative thinking ability between students who get mind mapping model based on optimization of right brain function and model of Problem Based Learning; (3) The average percentage of student responses shows that almost half of the students showed interest in the mind mapping model based on optimization right brain function and the Problem Based Learning model.